Indonesian Women’s Activism in Social Media: A Virtual Ethnography Study in the Instagram - Mashita Phitaloka Fandia Purwaningtyas (FISIP Universitas Atma Jaya Yogyakarta, 2021)
Instagram is widely used to create accounts for women’s activism. Some of thoseaccounts are managed by Indonesian, such as @indonesiafeminis, @perempuanbergerak, @womensmarchjkt, @perempuanberkisah.id, and @lawanpatriarki. They disseminate informationand knowledge on feminism, women empowerment, and gender equality among Indonesian youth.The research aims to analyze how the movements occur through Instagram and portrayals ofperspective on women empowerment. This research is conducted with the virtual ethnographymethod. This study finds that the movement of women’s activism accounts in social media platformsis deconstructed towards the common view of women empowerment and gender equality.